PENGARUH SUBSTITUSI TEPUNG GANYONG DENGAN TEPUNG AGAR TERHADAP SIFAT KIMIA, FISIK, DAN SENSORIS CANNA BAR - , GUPITA PRAMITASARI, Prof. Dr. Ir Y. Marsono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Canna flour is one of local flour that can be used to substitute wheat flour for some bakery products. To increase the fiber content of the flour powder agar can be added, but it might result in changing of the characteristic of the products. The aim of the research was to evalute the effect of substitution of canna flour with agar powder flour on the sensoric, physical and chemical properties of canna bar. Variation of 5, 10 and 15% of agar powder substitution were investigated. Sensoric properties were determine with attribute difference test method. Hardnes value was determined with Universal Testing machine, chemical composition were dermined using AOAC methode, soluble and insoluble fibres were measured with enzymatic gravimetric methode. The results showed that canna bar with 10% of agar flour substitution gave the most similar texture attributes with the commercial food bar. Increase of agar powder substitution increased the hardness value. Agar powder substitution affect the chemical properties. Substitution of 10% agar powder increased the Total Dietary Fiber from 7,31% to 12,31%.